Dynamics and Heterogeneity of Pb(II) Binding by SiO2 Nanoparticles in an Aqueous Dispersion - Goveia, Danielle [UNESP]; Pinheiro, Jose Paulo; Milkova, Viktoria; Rosa, Andre Henrique [UNESP]; van Leeuwen, Herman P. (Amer Chemical Soc, 2011)
Pb(II) binding by SiO2 nanoparticles in an aqueous dispersion was investigated under conditions where the concentrations of Pb2+ ions and nanoparticles are of similar magnitude. Conditional stability constants (log K) obtained at different values of pH and ionic strength varied from 4.4 at pH 5.5 and I = 0.1 M to 6.4 at pH 6.5 and I = 0.0015 M. In the range of metal to nanoparticle ratios from 1.6 to 0.3, log K strongly increases, which is shown to be due to heterogeneity in Pb(II) binding. For an ionic strength of 0.1 M the Pb2+/SiO2 nanoparticle system is labile, whereas for lower ionic strengths there is loss of lability with increasing pH and decreasing ionic strength. Theoretical calculations on the basis of Eigen-type complex formation kinetics seem to support the loss of lability. This is related to the nanoparticulate nature of the system, where complexation rate constants become increasingly diffusion controlled. The ion binding heterogeneity and chemodynamics of oxidic nanoparticles clearly need further detailed research.